PENGARUH METODE MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS NARASI PADA MATA PELAJARAN BAHASA INDONESIA PESERTA DIDIK KELAS V SD NASIONAL MAKASSAR - Ramlah Darwis; Muhammad Syahrul; Samsuddin Kade; Martini; Muh. Aidil Sudarmono R (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine narrative writing skills before and after using the mind mapping method, and to determine the method's effect on the writing skills of fifth-grade students at Makassar National Elementary School. This study used a quantitative approach with a pre-experimental design using a one-group pretest-posttest. The sample size was 20 students. Data collection used writing tests before (pretest) and after (posttest) the implementation of the mind mapping method. The results showed that narrative writing skills before using the mind mapping method were in the less skilled category with an average score of 51. After using the mind mapping method, writing skills improved to the skilled category with average scores of 80 and 85. The results of the hypothesis test from the results of the pre-test and post-test data analysis using the T-Test with an Asymp.Sig (2 tailed) value of 0.000 < 0.05, which means that there is a significant influence of the use of the mind mapping method on students' narrative text writing skills.